Kinematic analysis of the head and trunk movements of quadriplegic wheelchair athletes in the initial acceleration phase of the 100-m sprint: A case study - Kawabata, K.; Ibusuki, T.; Mitsui, T.; Kamijo, Y.; Tajima, F. (International Journal of Sport & Health Science, 2024)
The aim of this study was to investigate the relationship between wheelchair velocity and head and trunk movements by analyzing time series data of the initial acceleration phase of the 100-m sprint of three male quadriplegic wheelchair athletes in the T52 class. While sprinting 100 m at maximum effort, the athletes` propulsive movements were analyzed from start to 13 m using a motion capture system. In many strokes, wheelchair velocity increased slightly in the first half of the recovery phase and decreased tremendously in the second half. Peak angular velocity of trunk extension was observed in the first half of the recovery phase from release, and peak trunk extension angle was observed in the first half to the middle of the recovery phase. The results suggested that trunk extension contributes to increased wheelchair speed during the recovery phase. However, athletes in the T52 class are unable to perform active trunk extension due to their inability to demonstrate trunk muscle strength. It is speculated that the trunk extension observed in all of the present athletes is attributable to the reaction produced by pushing the hand-rims. Furthermore, the findings suggested that head movement is connected to trunk movement and is important for efficient trunk flexion/extension.